2020
DOI: 10.21203/rs.2.22617/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRIM3 inhibits P53 signaling in breast cancer cells

Abstract: BackgroundBeast cancer is the most common women cancer worldwide, while two third of them are ER alpha positive breast cancer. Among the ER alpha positive breast cancer, about 80% are P53 wild type, indicating the potential tumor suppression role in ER alpha positive breast cancer. Since P53 is an important safeguard to inhibit cell malignant transformation, reactivating P53 signaling could a plausible approach to treat breast cancer.MethodsTRIM3 protein levels were measured by western blot, while the P53 clas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
1
Order By: Relevance
“…Huang et al and Song et al suggested that TRIM3 is a tumor suppressor in the liver and cervical cancers, respectively [14,15]. However, Wang et al reported that TRIM3 plays a stimulating role in the MCF7 breast cancer cell line [16]. On the other hand, the study conducted by Marshall et al suggests that TRIM16 acts as a tumor suppressor in neuroblastoma cells [17].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al and Song et al suggested that TRIM3 is a tumor suppressor in the liver and cervical cancers, respectively [14,15]. However, Wang et al reported that TRIM3 plays a stimulating role in the MCF7 breast cancer cell line [16]. On the other hand, the study conducted by Marshall et al suggests that TRIM16 acts as a tumor suppressor in neuroblastoma cells [17].…”
Section: Open Accessmentioning
confidence: 99%
“…Yongzhen Li reports in his study that the oncogenic miR-4513 plays its role in MCF-7 cell line through inhibition of TRIM3, which leads to increased cell migration, invasion, colony formation and proliferation [19]. However, the study of Wang introduces the TRIM3 as an oncogenic factor in breast cancer, which promotes the proliferation of breast cancer cells through suppression of P53 signaling [20]. TRIM16 is suggested by Kim as a suppressor factor in breast cancer that reduces the viability of breast cancer cells [21].…”
Section: Open Accessmentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease. According to the expression of progesterone receptor (PR), estrogen receptor (ER), ERBB2 receptor (HER2), and Ki-67, breast cancer can be divided into fve groups: triple negative, HER2-enriched (non-luminal), Luminal B-like HER2+, Luminal A type, Luminal B type [3,4]. Clinically, adjuvant therapy using endocrine therapy and surgical treatment has markedly reduced Luminal A primary breast tumors death.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2017) and Song et al (2018) suggested that TRIM3 is a tumor suppressor in the liver and cervical cancers, respectively [14,15]. However, Wang et al (2020) reported that TRIM3 plays a stimulating role in the MCF7 breast cancer cell line [16]. On the other hand, the study conducted by Marshall et al (2010) suggests that TRIM16 acts as a tumor suppressor in neuroblastoma cells [17].…”
Section: Introductionmentioning
confidence: 99%